Inflation and Inflation Uncertainty Nexus in Kuwait: A GARCH Modeling Approach - Al-Zuhd, Tariq A.H.; Saleh, Mohammad H. (International Journal of Economics and Financial Issues, 2017)
In the this paper, we analyze the causality between inflation and inflation uncertainty in Kuwait . The monthly Consumer Price Index (CPI) during the period from January 1992 to September 2016 has been used to measure inflation. The inflation uncertainty is estimated by the conditional variances of inflation obtained using the Akaike, Schwarz information criteria and Hannan-Quinn Criteria. In order to ensure the robustness of the results, the Granger-causality technique is performed. The study findings show that the inflation significantly Granger-causes inflation uncertainty, supporting Friedman-Ball hypothesis. However, no empirical evidence is found to support the Cukierman - Meltzer hypothesis (1986) and only unidirectional relation is evident with causality running from inflation to inflation uncertainty. High volatility persistence for inflation is also confirmed. The findings of the study may be useful for policymakers at central bank to apply more efficient monetary measures. Keywords: Inflation, Inflation Uncertainty, GARCH model, Granger causality, Kuwait. JEL Classifications: D8, E31